Psychotherapy as abuse: Jehu, D (with Davis, J, Garrett, T, Jorgenson, L M, & Schoener, G R) (1994) Patients as victims: Sexual abuse in psychotherapy and counselling. Chichester: John Wiley. 241pages. ISBN 0-47194398-3 pbk. - Collings, Steven J (PINS-Psychology in Society, 2026)
Derek Jehu and his associates set out to provide a concise presentation of the issues and regulatory provisions regarding the sexual abuse of patients by mental health professionals in the United States and the United Kingdom. In Section 1 of the text the reader is introduced to some of the major issues and controversies in the field. The first of these issues relates to the difficulties involved in defining sexual abuse. Although there is a general consensus in the literature that explicit sexual acts (sexual intercourse, genital fondling, etc) between a therapist and client, in the context of ongoing therapeutic contact, are always improper/abusive, there is less agreement as to the propriety of other forms of intimate behaviour (e.g., touching or hugging). As Jehu points out, behaviours such as touching may be appropriate in some circumstances (e.g., when used as an expression of reassurance, support or comfort) but not in other circumstances (e.g., when therapists use touch to evoke sexual arousal in themselves, when touch is used by therapists as a transitional step in a sequence towards more intimate sexual involvement, or when touch is used with patients who are likely to incorrectly perceive nurturant touching as sexual/abusive in nature).